2005
DOI: 10.1162/0898929054985400
|View full text |Cite
|
Sign up to set email alerts
|

Who Comes First? The Role of the Prefrontal and Parietal Cortex in Cognitive Control

Abstract: Abstract& Cognitive control processes enable us to adjust our behavior to changing environmental demands. Although neuropsychological studies suggest that the critical cortical region for cognitive control is the prefrontal cortex, neuroimaging studies have emphasized the interplay of prefrontal and parietal cortices. This raises the fundamental question about the different contributions of prefrontal and parietal areas in cognitive control. It was assumed that the prefrontal cortex biases processing in poster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
142
4
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(169 citation statements)
references
References 43 publications
22
142
4
1
Order By: Relevance
“…It is possible that the left DLPFC is also necessary for context updating but follows a different time course and was thus unaffected by a disruption within the tested time window (15,44). However, the lateralization we observed in the TMS study was predicted by the source localization of an event-related potential (ERP) observed in our previous EEG study, which was associated with the updating of context in the same task (18).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…It is possible that the left DLPFC is also necessary for context updating but follows a different time course and was thus unaffected by a disruption within the tested time window (15,44). However, the lateralization we observed in the TMS study was predicted by the source localization of an event-related potential (ERP) observed in our previous EEG study, which was associated with the updating of context in the same task (18).…”
Section: Resultsmentioning
confidence: 62%
“…Several studies have documented the updating of context information in PFC (11)(12)(13)(14)(15)(16)(17)(18). However, few studies have addressed the mechanisms by which this is accomplished.…”
mentioning
confidence: 99%
“…A role for posterior parietal cortex in processing response alternatives finds additional support in the broader cognitive control literature (37,38). A temporal shift from mid-VLPFC (conceptual) to inferior parietal (response) cortex may also parallel electroencephalogram evidence that TS is accompanied by an early frontal component (Ϸ300-500 ms) followed by a subsequent parietal component (Ϸ500-1,000 ms) (39)(40)(41).…”
Section: Resultsmentioning
confidence: 88%
“…However, fMRI and electroencephalographic studies in humans also implicate parietal cortex and presupplementary motor cortex (pre-SMA) (medial BA 6) in task switching (Dreher and Berman, 2002;Sohn et al, 2003;Rushworth et al, 2005), and transcranial magnetic stimulation studies in humans have shown that transient stimulation of parietal cortex or pre-SMA/medial wall leads to a slowing in the ability to switch from one task to another (Rushworth et al, 2001;Rushworth et al, 2002). A recent electroencephalographic study in humans shows that activity in the lateral prefrontal cortex precedes activity in parietal cortex during the updating of task rules (Brass et al, 2005b), supporting the hypothesis that lateral prefrontal cortex provides an abstract task representation that is then transmitted to, and/or further specified in, posterior cortices (Brass and von Cramon, 2004;Stoet and Snyder, 2004).…”
Section: Flexible Rule Usementioning
confidence: 99%